Research progress on formation mechanism of health factor 2,3,5,6-tetramethylpyrazine in Baijiu - HU Zhihui, CHEN Fang, GUO Xuefeng, ZHAO Tengfei, LUO Zhenbiao, WU Deguang (Zhongguo niangzao)
2,3,5,6-tetramethylpyrazine (TTMP) is the main active ingredient of traditional Chinese herbal medicine Ligusticum sinense 'Chuanxiong', which has various pharmacological effects such as relieving wind and pain, regulating Qi, and promoting blood circulation and resolving stasis, treating cardiovascular and cerebrovascular diseases. At present, TTMP has been detected in sauce-flavor (Jiangxiangxing) Baijiu, sesame-flavor (Zhimaxiangxing) Baijiu and others, which has become one of the health factors in Baijiu. How to increase the content of TTMP without affecting the flavor of Baijiu will be an effective mean to improve the quality of Baijiu, and exploring its formation mechanism and influencing factors of TTMP synthesis will be of utmost importance. The article mainly reviewed the achievements in exploring the formation mechanism of TTMP in recent years, and concluded that microbial synthesis of TTMP was mainly divided into two stages: synthesis of intermediate metabolites, followed by chemical reactions to synthesize TTMP, of the two, chemical reactions synthesis being the main focus that limited the production of TTMP synthesis. In response to the problem of low synthesis efficiency, this article introduced solutions which contain the screening of high yielding microbial strains, modifying metabolic pathways and optimizing the fermentation conditions and so on. The idea of replacing low efficient 'chemical reactions synthesis' with high efficient 'enzymatic synthesis' was proposed, and the strategy of de novo synthesis of TTMP by heterologous constructed microorganisms was proposed, which was of great significance to further explain the formation mechanism of TTMP in Baijiu, and further improve the quality and efficiency of Baijiu and lead the concept of 'healthy Baijiu'.